(untitled) (Tokyo, 1979)
Part I: Politics, Part II: Economics, The book describes the dynamics of interaction between Japan's leading economic and political groups. One essay probes the decision-making process in foreign policy formulation; others review Japanese management methods.
Keywords: Politics and government,Chính trị và chính phủ; Japan,Nhật Bản